SYNTHESIS OF CATION EXCHANGERS USED FOR WASTEWATER TREATMENT FROM METHYLNAPHTHALENE - F. Sh. Boboqulova; N. Raxmatova (European Science Publishing, 2025)
This article investigates the process of separating naphthalene homologs from pyrolysis oil. The composition of the pyrolysis oil was analyzed using chromatographic methods, and optimal conditions for separation were determined. The oxidation processes of naphthalene homologs to synthesize naphthalene carboxylic acid were studied. The oxidation kinetics of naphthalene homologs and the composition of the resulting products were examined using infrared spectroscopy (IR), thermogravimetric analysis (TG), and chromatographic techniques. These findings are highly valuable for the application of naphthalene derivatives in organic synthesis.
Keywords: Pyrolysis oil, naphthalene homologs, oxidation, catalysis, infrared spectroscopy, thermogravimetry, fractional separation, chromatography, naphthalene carboxylic acid, polycondensation, polymethylenenaphthalene carboxylic acid, extraction.